Bacteriological Etiologic Diagnosis, Mode of Infection and Management of Chronic Osteomyelitis: A Prospective Hospital-Based Study in Bangladesh (Bangladesh Journal of Medical Microbiology, 2023)
Background: There are different factors responsible for chronic osteomyelitis.Objective: The purpose of the present study was to find out the bacteriological aetiology of chronic osteomyelitis patients.Methodology: This prospective hospital-based study was conducted in the Department of Orthopaedic and Traumatology at Cox’s Bazar Medical College Hospital, Cox’s bazar, Bangladesh from January 2019 to June 2022 for a period of three and half years. Eligible patients for enrolment in the present study had to sustain an osseous infectious process confirmed by radiological findings lasting more than 2 weeks without acute symptomatology or few contributory laboratory results. The bacteriological aetiology were recorded and the antimicrobial sensitivity testing were performed by dis diffusion test.Results: A total number of 89 cases of osteomyelitis patients were recruited for this study. The mean age with the SD of study population was 11.5±7.89 years with the range of 1 to 42 years. Infected scabies was the most common cause osteomyelitis among the study population which was 42.0% cases in children group; however, there was no cases in adult group. Otitis media, rhinitis dental caries were also found among the children which were 25.0% cases, 5.0% cases, 18.0% cases respectively. Among adult group implant surgery was the most common cause of osteomyelitis which was 65.0% cases. Most common bacterial isolate was Staphylococcus aureus which was 29(32.6%) cases. Coagulase Negative Staphylococcus (CoNS) and Proteus species were the second most common isolated bacteria which was 17(19.1%) cases in each. Gram negative bacteria like Escherichia coli and Pseudomonas species were the most common isolated bacteria which were 11(12.4%) cases and 9(10.1%) cases respectively.Conclusion: In conclusion implant surgery is the most common cause of osteomyelitis and Staphylococcus aureus is the most common isolated bacteria.Bangladesh Journal of Medical Microbiology, January 2022;16(1):8-13